2014
DOI: 10.1016/j.fitote.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolites of isorhynchophylline in rats and their neuroprotective activities in the HT22 cell assay

Abstract: Isorhynchophylline is one of the major alkaloids from the Uncaria hook possessing the effects of lowered blood pressure, vasodilatation and protection against ischemia-induced neuronal damage. However, the metabolic pathway of isorhynchophylline has not been fully reported yet. In this paper, the metabolism of isorhynchophylline was investigated in rats. Five metabolites were isolated by using solvent extraction and repeated chromatographic methods, and identified by spectroscopic methods including UV, MS, NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…Secondly, phytochemicals, such as tablets of Uncaria rhynchophylla total alkaloids, containing chloride salts of rhynchophyllinoid alkaloids have been used for several decades in clinical situations to treat hypertension, headache, and stroke in China. Thus, the oxidation at C-5 should be the major metabolic pathway for tetracyclic oxindole alkaloids, which is consistent with our last study of the metabolic fate of IRN in rats orally given IRN [36].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Secondly, phytochemicals, such as tablets of Uncaria rhynchophylla total alkaloids, containing chloride salts of rhynchophyllinoid alkaloids have been used for several decades in clinical situations to treat hypertension, headache, and stroke in China. Thus, the oxidation at C-5 should be the major metabolic pathway for tetracyclic oxindole alkaloids, which is consistent with our last study of the metabolic fate of IRN in rats orally given IRN [36].…”
supporting
confidence: 90%
“…M-6 was the epimer of M-0 that is believed to be formed through the isomerization at C-7 in rats after the oral administration of ICN. IRN is reported to undergo isomerization at the spiro center to form RN in rat urine after oral administration of IRN by our last study [36]. In addition, the isomerization at the spiro centre of rhynchophylline-type oxindole alkaloids in vitro was recognized by Wenkert et al as early as 1959 and a retro-Mannich ring opening, rotation, and Mannich ring closure was proposed as the mechanism involved.…”
mentioning
confidence: 79%
“…In the studies by Wang et al [12,13] R or IR was found in the plasma, bile, urine and feces together with 10-or 11-hydroxy-R or -IR and their 10-or 11-O-glucuronides found in bile as well as 10-or 11-hydroxy-R or IR found in urine and feces after oral administration of R or IR to rats. We isolated and structurally identified five urinary metabolites in rats given oral IR [14]. Huang et al [15] found four phase II metabolites in the bile of rats given IC orally, although their conjugated positions could not be confirmed.…”
Section: Introductionmentioning
confidence: 95%
“…C, corynoxeine-N-oxide (C-NO), 18,19-dehydrocorynoxinic acid (DCA), 18,19-dehydrocorynoxinic acid B (DCAB), isocorynoxeine-N-oxide (IC-NO), IC, IR and R were isolated from the CHCl 3 extract of U. rhynchophylla [1,8,20] were isolated from the urine of rats administered IC orally [14]. The identification of these compounds was confirmed by spectral analysis including UV, 1D and 2D NMR, mass spectrometry (MS) and circular dichroism experiments (CD).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Different from above compounds, hirsutine (1) and hirsuteine (2) only produced their 11-hydroxy metabolites in rats (Nakazawa et al, 2006). Recently, Chen et al 2014 andQi et al, 2015 reported that the possible oxidation and hydroxylation metabolites of isorhynchophylline (40) and isocorynoxeine (78), which was important to further understand their metabolites Qi et al, 2015). Kushida et al (2013) further investigated the pharmacokinetics of Uncaria hook alkaloids after oral administration of Yokukansan (0.25, 1 and 4 g/kg).…”
Section: Pharmacokinetic and Metabolismmentioning
confidence: 99%